Pengaruh Metode Card Short Terhadap Motivasi Belajar Dan Hasil Belajar Siswa Pada Mata Pelajaran Al-Qur’an Hadis Kelas VII Di SMPIT Sahabat Qur’an Kota Sawahlunto - Agusli, Gunawan; Charles, Charles (Faidatuna, 2023)
This research was motivated by the low level of encouragement and results of practicing the Quran Hadith for category VII students at SMPIT Kawan Quran. The aim of this research is to identify the impact of the card sort procedure in the main review of strengthening my faith by worshiping the encouragement and results of practicing the Qur'an Hadith at SMPIT Kawan Qur'an, Sawahlunto City. This type of research is imaginary research, with the concept of randomized control group only design research. Based on research results, it was found that in general the encouragement of students for each marker was in the range of 80% - 84% with a large classification and in general the percentage of encouragement for students to practice Al-Quran Hadith after applying the Card sort procedure was 82% with a large classification also. On the other hand, students' results for practicing the Qur'an, the Words of the Prophet in the research category were 82.08 with a completion percentage of 72%. On the other hand, in general what was obtained in the supervision category was 73.72 with a completion percentage of 56%. From the calculations we get tcount= 2.67 and ttable= 2.02. Because tcount ttable until H1 is obtained. So, it can be said that the results of students' training with the application of card sort procedures are better than conventional training in the subject of the Qur'an, Words of the Prophet, category VII SMPIT Kawan Quran, Sawahlunto City.